Prevalencia de signos y síntomas de trastornos temporomandibulares de tipo muscular y del complejo cóndilo disco en habitantes de la vereda la Cecilia, Villavicencio-Meta - Beltrán Celis, Jaime Alberto; Carrillo Vargas, Dayana Katherin (Universidad Antonio Nariño, 2022)
Introduction: The ADA defines temporomandibular disorders (TMD) as any functional alteration of the stomatological system, among the main signs and symptoms of TMD are pain and joint noises. In Colombia, the studies that report the presence of signs and symptoms of TMD are few and the last report of the ENSAB on the state of the temporomandibular joint (TMJ) is in the ENSAB III and this study was carried out in 15 year olds. Objective: The objective of this research was to evaluate the presence of signs and symptoms of TMJ and alterations of the condylar disc complex in inhabitants of the village of La Cecilia, Villavicencio-meta.